Temperature and pH define the realised niche space of arbuscular mycorrhizal fungi. Issue 2 (4th March 2021) - Davison, John; Moora, Mari; Semchenko, Marina; Adenan, Sakeenah Binte; Ahmed, Talaat; Akhmetzhanova, Asem A.; Alatalo, Juha M.; Al‐Quraishy, Saleh; Andriyanova, Elena; Anslan, Sten; Bahram, Mohammad; Batbaatar, Amgaa; et al.
Summary: The arbuscular mycorrhizal (AM) fungi are a globally distributed group of soil organisms that play critical roles in ecosystem function. However, the ecological niches of individual AM fungal taxa are poorly understood. We collected > 300 soil samples from natural ecosystems worldwide and modelled the realised niches of AM fungal virtual taxa (VT; approximately species‐level phylogroups). We found that environmental and spatial variables jointly explained VT distribution worldwide, with temperature and pH being the most important abiotic drivers, and spatial effects generally occurring at local to regional scales. While dispersal limitation could explain some variation in VT distribution, VT relative abundance was almost exclusively driven by environmental variables. Several environmental and spatial effects on VT distribution and relative abundance were correlated with phylogeny, indicating that closely related VT exhibit similar niche optima and widths. Major clades within the Glomeraceae exhibited distinct niche optima, Acaulosporaceae generally had niche optima in low pH and low temperature conditions, and Gigasporaceae generally had niche optima in high precipitation conditions. Identification of the realised niche space occupied by individual and phylogenetic groups of soil microbial taxa provides a basis for building detailed hypotheses about how soil communities respond to gradients and manipulation in ecosystems worldwide. Abstract : See also the Commentary on this article by Kivlin et al., 231 : 508–511 .